Avaliação multimodal de habilidades sociais de estagiários de psicologia clínica e suas relações com a qualidade dos atendimentos - Sartori, Raquel Martins (2018)
The literature in the theoretical-practical field of Social Skills Training has indicated a positive relationship between a well-developed repertoire of social skills and the quality of social and professional relationships. The profession of psychologist social in nature, as most of the work occurs via interpersonal relations, and requires from the professional an elaborated repertoire of skills and competencies to handle generally conflictive relationships. Considering that the management of social interactions is an essential part of a psychologists’ work, the social competence of professionals can be as important as their technical competence. Multimodal evaluation of psychologists’ social skills repertoire and social competence would help to identify important skills for the quality of the therapeutic process, considering their relevance to the interpersonal nature of psychologists’ work. Therefore, this research aims to evaluate the potential relationship between skills and social competence of Clinical Psychology trainees and the quality of the clinical care they after. In total, 27 students from a Psychology course, their respective internship supervisors in Clinical Psychology, clients and informants indicated by them participated in the study. In the fourth year of their graduate studies, a multimodal evaluation of the students social skills repertoire was carried out, including self-assessment and a peer evaluation using the Social Skills Inventory, a sociometric evaluation, interviews and behavioral observation in a structured situation like reality. In the fifth year of the program, the quality of the clinical services provided by the students was evaluated based on the formation of a therapeutic alliance with their clients, progress of their clinical cases, and supervisors’ evaluations of the students' performance during the care. The data were statistically analyzed using tests of correlation and regression. The results point to positive associations between communication skills, self-control of aggressivity and expression of positive feelings in the formation of an alliance with clients and based on supervisor evaluations. Negative associations were also found between social skills and care quality, especially for the ability to interact with unknown people, to praise others and to disagree with higher authorities. The data allow us to know which social skills are associated with indicators of quality of care, however, further work is needed to better investigate the students’ social competence. Considering the multidimensionality of social skills and the negative associations found in this research, it is suggested that other aspects of social performance need to be investigated, for example, investigation criteria and requirements for social competence via the amplification of these assessment measure are needed. The cultural values of each subgroup define very particular norms for interaction, which need to be made explicit to meet social competence criteria and establish successful relationships. Despite the limitations of this research, among them the restricted number of participants and the absence of specific instruments for the evaluation of professionals’ social skills and social competence, the relationship between social skills and the quality of care was evaluated. Future research on this issue will contributes to the improvement of information on the subject.